(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aims to demonstrate the impact of using the Time Driven - Activity Based Costing technique as one of the most important strategic cost management techniques to achieve competitive priorities for the economic unit through its application in the Kufa Cement Factory, one of the factories of the Iraqi General Cement Company. To achieve this goal, the researcher relied on the data he obtained from During field visits and review of the factory records for the year 2018, as well as conducting personal interviews with the management and workers in the factory from all specialties, the research adopted the applied method to test the research hypothesis and reach a set of conclusions, the most important of which is the Kufa Cement Factory’s reliance on the number of workers as a cost vector in distributing costs. Indirect industrial, which is included in calculating the cost of one ton of cement, which in turn leads to achieving unfair results in the calculation, resulting in misleading information that is reflected in making inappropriate decisions for people who may rely on cost information in this regard, as well as high production costs. Due to the increase in the number of workers and the lack of optimal exploitation of the available energy, in addition to the presence of large idle energy in the laboratory in the field of research, which was not taken into account by those in charge of the laboratory. The most important findings of the researcher can also be summarized in a set of recommendations, the most important of which is the necessity of optimal exploitation of the resources available in the laboratory and the field of research in order to achieve cost savings through the use of modern techniques, including the Time Driven - Activity Based Costing technique to exploit those resources efficiently and effectively, which will be reflected in the laboratory should also adopt and apply the research field for (TD-ABC) in order to reduce the cost of the product by more than half. It also suits the modern business environment in terms of providing detailed information about the product costs and helps management identify untapped resources for the purpose of Optimum exploitation. This technique also has a significant impact on price flexibility and thus achieving competitive priorities for the cement product in light of price competition.